Analysis and evaluation of nutritional intake and nutrition quotient of Korean athletes with disabilities in the Tokyo Paralympic Games - Jeoung, B.; Kim, J. (Nutrients, 2021)
This study analyzed and evaluated the nutritional intake and nutrition quotient for adults (NQ-A) among 21 disabled national athletes preparing for the Tokyo Paralympic competition. A 24-h recall nutrition survey was conducted on the second day of training and one day of the weekend (holidays) to analyze daily nutritional intake. Dietary information was analyzed using the NQ-A questionnaire, which comprises 21 items. The athletes were divided into three groups based on the NQ-A score (High, Middle, Low). A comparative analysis of dietary intake of disabled athletes with the recommended dietary intake amount (RDA) was performed. The intake of carbohydrates (166.9%), proteins (112.3%), vitamin E (112.0%), thiamine (124.6%), riboflavin (100.2%), vitamin B6 (110.6%), vitamin B12 (120.7%), sodium (216.6%), phosphorus (118.3%), iron (146.5%), iodine (143.2%), and selenium (114.2%) was higher than the Korean-recommended amount. In particular, as the results of comparing dietary intake between the three groups showed, the low NQ-A score group had significantly lower intake compared to the %RDA for vitamin E (67.1%), C (26.3%), and Potassium (42.8%). However, with most nutrients, nutritional intake deficiency was not shown to be a problem.